GRACE observes the natural and irrigation-induced regional redistribution of water storage in Central Asia - Abror Gafurov; Valeria Selyuzhenok; Milena Latinovic; Heiko Apel; Adkham Mamaraimov; Abdulkhakim Salokhiddinov; Eva Boergens; Andreas Güntner (Journal of Hydrology: Regional Studies)
Study Region: Central Asia region, where snow and glacier covered Tian Shan and Pamir mountains serve as “Water Tower” to supply populated areas downstream with essential freshwater resources, predominantly for agricultural production in summer and for energy production in winter. Study Focus: To identify the impact of irrigation practices on large-scale water storage by analyzing the spatial dynamics of water storage in Central Asia from sink to source using satellite-based Terrestrial Water Storage (TWS) variations from six GRACE(-FO) solutions and snow cover from MODIS. New Hydrological Insights for the Region: Snow Cover Index (SCI), a new proxy index for snow accumulation shows that GRACE-based TWS dynamics agree very well with snow accumulation and melt for seasonal and inter-annual variations. The spatial patterns of seasonal TWS variations show water re-distribution from the mountain region to the downstream parts, where agricultural fields are irrigated. In these areas, the maximum storage in summer observed with the majority of GRACE solutions can be attributed to the diversion of water inflow from the mountain ranges into vast areas of agricultural land. The ability of GRACE to observe both natural and human-induced water re-distribution in Central Asia indicates its potential for regional-scale monitoring applications in water resources management.